PHYSIOLOGICAL ADAPTIVE MECHANISMS OF LEYMUS CHINENSIS DURING GERMINATION AND EARLY SEEDLING STAGES UNDER SALINE AND ALKALINE CONDITIONS - J. Lin; C. Mu; Y. Wang; Z. Li; X. Li (Journal of Animal and Plant Sciences, 2014)
Germination and early seedling growth are the most critical periods for plant establishment in saline-alkaline soil, the main factor limiting plant growth and production worldwide. To explore the physiological adaptive mechanisms of the two stages under saline and alkaline conditions, Leymus chinensis was tested by mixing two neutral salts (NaCl: Na2SO4) and two alkaline salts (NaHCO3: Na2CO3). Results showed that reductions of germination and seedling growth were greater under alkaline stress. Nongerminated seeds germinated well after transferring from higher salinity and lower alkalinity to distilled water. The Na+ concentration, Na+/K+ ratio increased but K+ concentration decreased under both stresses, and the changes were greater under alkaline stress. Under saline stress, seedlings mainly accumulated Cl- and soluble sugars to maintain osmotic and ionic balance. But alkaline stress restrained the absorptions of Cl-, NO3– and H2PO4-, enhanced organic acids, especially malic acid and citric acid to supply the shortage of inorganic anions, and accumulated more soluble sugars to cope with osmotic stress from the high Na+ concentration. Thus, our results suggested that the deleterious effects of alkaline stress are more severe than saline stress, high salinities only delay most seeds germination, but high alkalinities cause them lose viability. Accumulating organic acids is the primary different adaptive mechanism to saline and alkaline stresses during early seedling stage of Leymus chinensis. A better understanding of the germination and early seedling processes should facilitate the effective utilization of this species under salt and alkali environments.
Keywords: Seed germination; Germination recovery; Organic acid; Alkaline stress; Saline stress